(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
In 2011, we conducted a nationwide survey exploring the ideal traits of early childhood educators. Overall, 13.9% (N=920) of all the educators filled out the survey. Content analysis was performed using the Maxdictio extension of the MAXQDA-12 (VERBI GmbH) package. The professional characteristics emerging from the survey are compared with the training and outcome requirements of infant and early childhood education courses, including necessary knowledge, skills, attitudes, and autonomy, described in order 18/2016 (VIII. 5.) of the Hungarian Ministry of Human Capacities (EMMI).